PENGADOPSIAN STANDAR LAPORAN KEUANGAN SEBAGAI PEMEDIASI HUBUNGAN ANTARA LITERASI KEUANGAN DAN INKLUSI KEUANGAN TERHADAP KINERJA UMKM DI KOTA PEMATANGSIANTAR - hery silitonga; Ruth Tridianty Sianipar; Juan Anastasia Putri; Robert Tua Siregar (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to determine the adoption of financial reporting standards in mediating the relationship between financial literacy and financial inclusion on the performance of MSMEs in Pematang Siantar City. Library and field research design with a quantitative approach. The research subjects taken in this study were MSME actors in Pematangsiantar City. The research was carried out in eight sub-districts in Pematangsiantar City. Data collection techniques using observation, interviews, questionnaires and documentation. The data analysis method used is Partial Least Square (PLS). The data analysis test tool uses the Smartpls statistical software. The results obtained were positive and significant between financial literacy and the adoption of financial reporting standards, financial literacy and MSME performance, financial inclusion and MSME performance, adoption of financial reporting standards and MSME performance, and positive and insignificant results between financial inclusion and adoption of financial reporting standards. the results of moderation obtained by the variable adopting financial reporting standards are proven to be able to mediate the relationship between financial literacy and MSME performance